Processo de avaliação de software aplicado à seleção de sistemas gerenciadores de conteúdo - Menezes, Jislane Silva Santos de (2016)
Content Management Systems (CMS) are information systems used to facilitate the maintenance of content on the Internet using a central interface. This ease of use allows users of organizations without programming knowledge and software development make use of this type of system. Over the years, the CMSs progressed to robust development platforms that have provided a wide range of added features. There are CMSs of the most varied characteristics, free or commercial applications developed using programming languages such as Java, PHP, Python and dotNET using various database management systems such as Oracle, MySQL , SQL Server and Postgree. Considering the importance of acquiring a solution that meets user expectations among many CMSs available, ISO/IEC 25040 provides a process for evaluating quality of the software product for developers, acquirers and independent evaluators. This evaluation process is based on a number of criteria. This research project proposes an approach to identify, analyze and classify tools Content Management System , according to development criteria and maintenance websites to governmental organizations, based the model proposed by ISO/IEC 25010 and technology acceptance model (TAM). Using the methodology proposed by ISO / IEC 25040, the CMSs were identified by means of literature and two evaluation approaches were defined approaches based on functional and non functional requirements and based on TAM. The definition of criteria was created from interviews and questionnaires with stakeholders. As case study, five CMSs open source and free participate of the evaluation process under the two approaches to meet the needs of EMGETIS government company. To perform the evaluation questionnaires were created and the measurement was performed by using descriptive statistics of variables such as frequency, positive count and average on the results of evaluations. TAM approach has also evaluated the relationship between your variables through the coefficient of Spearman. Finally, a comparison between the CMSs for each approach was generated. The Plone CMS answered the highest number of requirements in the evaluation requirements. The WordPress CMS had the best result in TAM approach. The XOOPS CMS had lower attendance in the two approaches. The EMGETIS chose the Wordpress CMS, because besides the ease of use and installation, the CMS was developed in PHP language that the company already has knowledge and the secretariats was getting training to use. The research was funded by Fapitec in partnership with EMGETIS and participates in the Program of Support and Development of Public Policy for the State of Sergipe contributing to the process of selection and acquisition of CMSs for public departments of the state.